Virtues, Resilience, and Well-Being of Indigenous Youth in Peru - R. L. Bullock, Abigail; Stumpf, B. Cameron; Chang, Kelly B. T. (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2021)
Objectives: The objective of this study was to observe the relation of Values In Action (VIA) virtues, well-being, and resilience within a unique, non-Western population of Indigenous youth in the Peruvian Amazon.Methods: Data were collected from students (n = 172, age range: 11-16 years) attending a rural village school via self-report surveys to assess relationships using the VIA Youth-96 (VIA-Y-96) Assessment, Personal Wellbeing Index (PWI-A), and the Child and Youth Resilience Measure (CYRM-28).Results: The factor analysis of the CYRM-28 yielded a 3-factor breakdown (Social Engagement, Cultural Citizenship, and Guidance) instead of eight. Different VIA virtues predicted each of the three factors of the revised 3-factor CYRM-21-Peru model (CYRM-21-P); Transcendence, Humanity, and Wisdom were predictors of well-being; and higher reported resilience leads to higher well-being. Most participants scored very high on the PWI-A. Implications: Research presented in this paper involved a unique population of Indigenous youth residing in the Peruvian Amazon, and found that (a) VIA virtues were differentially associated with well-being, (b) Humanity was a significant predictor across Cultural Citizenship and Social Engagement in the revised CYRM-21-P, and (c) higher resilience was correlated with higher well-being. Implications of this research can be used to inspire future research of Indigenous populations in a Latin American context to develop youth development programs that teach students from a strength-based perspective to improve vocational, academic, psychological, and social well-being.